Indonesian Fintech Business: New Innovations or Foster and Collaborate in Business Ecosystems? - Teja, Adrian (The Asian Journal of Technology Management (AJTM), 2017)
Abstract. There are many innovative products fail to reach minimum critical mass adopter and cease to exist. New financial technology products are not an exception because the current financial technology to facilitate transactions, whether payment, investment, and insurance still function remarkably well. Since new financial technology products have features to better serve low to middle-level customers in the form of higher convenience level and lower costs than the current financial technology products, the initiatives to ensure their success is imperative. Thus, the purpose of this study is to present propositions based on a literature review to encourage companies to simultaneously have two competencies, first competencies in new product development and second, competencies to foster and collaborate with other companies in within and across business ecosystems. The implications of this paper are companies with higher competencies to foster and collaborate with other companies, even though they start with relatively basic innovative product, have higher probability to reach minimum critical mass of adopter and higher probability to become leader in their business ecosystem and government need to maintain their active role to foster collaboration within and across business ecosystem. Â Keywords: Business ecosystem, business ecosystems leader, collaboration, fintech (financial technology), new product development.